RELATIVE EFFECTIVENESS OF COOPERATIVE AND INQUIRY LEARNING METHODS ON STUDENTS’ ACADEMIC ACHIEVEMENT AND RETENTION IN BASIC ELECTRICITY (NAU Journal of Technology and Vocational Education, 2024)
The study investigated the relative effectiveness of cooperative and inquiry learning methods on students’ academic achievement and retention in Basic Electricity. Cooperative learning is an active learning method where students are arranged in pairs or small groups to help each other learn assigned material, while Inquiry learning is also a form of active learning method where progress is assessed by howwell students develop experimental and analytical skills rather than how much knowledge theypossess. Two research questions guided the study while two nullhypotheses were tested at 0.05 level of significance. Quasi-experimental research design was adopted for the study, specifically, non-equivalent experimental group design. The study was carried out in Awka and Aguata Education Zones of Anambra State. The population consisted of all the 413 NTC II students offering Basic Electricity in the 12 technical colleges in Anambra State. The sample for the study comprised 60 National Technical College year II (NTC II) students from two intact classes in two Technical Colleges in two Education Zones, drawn using multi- stage sampling procedure. Basic Electricity Achievement Test (BEAT) was the instrumentused for data collection. The instrument was validated by the experts and reliability test was conducted using Kuder- Richardson 21 formula. The reliability index was established at 0.80. The experimental group1 were taught Basic Electricity using cooperative learning method, while experimental group 2 was taught using inquiry learning method. The treatments lasted for five weeks. Data collected were analysed using mean, standard deviation and Analysis of Covariance (ANCOVA). The results revealed that cooperative learning method was more effective than inquiry learning method in facilitating students’ academic achievement and retention in Basic Electricity. Based on the findings of the study, it was recommended among others, thatcooperative learning method should be formally adopted in technical colleges, secondary and vocational schools for instruction in Basic Electricity to improve the academic achievement and retention ability of students.
Keywords: Cooperative learning method, Inquiry learning method, Basic Electricity, Academic achievement, retention.